2021
DOI: 10.3389/fpls.2021.757516
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Investigation of Chalcone Synthases Based on Integrated Metabolomics and Transcriptome Analysis on Flavonoids and Anthocyanins Biosynthesis of the Fern Cyclosorus parasiticus

Abstract: The biosynthesis of flavonoids and anthocyanidins has been exclusively investigated in angiosperms but largely unknown in ferns. This study integrated metabolomics and transcriptome to analyze the fronds from different development stages (S1 without spores and S2 with brown spores) of Cyclosorus parasiticus. About 221 flavonoid and anthocyanin metabolites were identified between S1 and S2. Transcriptome analysis revealed several genes encoding the key enzymes involved in the biosynthesis of flavonoids, and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The purified recombinant proteins encoded by the empty pET‐32a vector were used as the negative control. The enzyme assay process and HPLC parameters were consistent with the previously reported studies (Niu et al, 2021). To analyze the effect of the reaction temperature on ScCHS1 activity, the reaction was screened using the different temperatures (20–60°C) at phosphate buffer (pH 6.5).…”
Section: Methodssupporting
confidence: 88%
See 4 more Smart Citations
“…The purified recombinant proteins encoded by the empty pET‐32a vector were used as the negative control. The enzyme assay process and HPLC parameters were consistent with the previously reported studies (Niu et al, 2021). To analyze the effect of the reaction temperature on ScCHS1 activity, the reaction was screened using the different temperatures (20–60°C) at phosphate buffer (pH 6.5).…”
Section: Methodssupporting
confidence: 88%
“…Then CHSs from ferns and seed plants appeared and clustered into a large branch. ScCHS1 was grouped together with two CHS from ferns LoCHS1 (MK216767) (Ni et al, 2020) and CpCHS1 (OK136250) (Niu et al, 2021), and located in the root of the CHS/STS (stilbene synthase) sub-clades from seed plants (Figure S2). These results suggested that the evolution of CHS was consistent with the evolutionary status of the different species.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations